STUDI LAJU KOROSI DAN MEKANISME INHIBISI ALUMINIUM MURNI MENGGUNAKAN NATRIUM SITRAT - Siregar, Tiurlina (Jurnal Kimia (Journal of Chemistry), 2013)
The process of corrosion in metals is a spontaneous one that goes along with the flow of the electrons in the metal that serves as the anode to that which act as a cathode. Thus, metal corrosion is an electrochemical process. A common form of corrosion on aluminum is pitting corrosion. Pitting corrosion can occur on metal surfaces in direct contact with moist air, usually with a metal that has a thin layer of oxide. Because of the a corrosions, a variety of processes in the metallurgical industry should get special treatment to improve the corrosion resistance of the environment, ie with the addition of a corrosion inhibitor. A corrosion inhibitor is an additive in the fluid that can slow the rate of corrosion. Sodium citrate is an anodic inhibitor which is an ampifilik organic salt with both polar and non-polar groups. Sodium benzoate and sodium tartrate salt are ampifilic known as food additive, show that salts can act as corrosion inhibitor on aluminum. These findings drive the author to try Sodium Citrate as a corrosion inhibitor on aluminum which is environmentally friendly given that the benzoate salt at high levels the can’t damage environment.
Keywords: Corrosion, Inhibition, Aluminum and Sodium Citrate